Analisis Kemampuan Representatif Matematis dalam Operasi Penjumlahan, Pengurangan, Perkalian, dan Pembagian pada Siswa Kelas III Sekolah Dasar - Muhammad Dzulkifli; Salmaini Safitri Syam; Chandra Chandra (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
Mathematical representative ability is a person's ability to express mathematical ideas, objects, and relationships in various forms of representation, both visually, symbolically, verbally, and contextually. This study aims to analyze the mathematical representative ability of students through counting operations in grade III elementary school in the form of story problems. The method used was descriptive qualitative research with written test instruments to assess cognitive abilities and observation to assess psychomotor skills. The research subjects consisted of five grade III elementary school students, by giving test questions on mathematical reasoning skills, observing students directly in solving and understanding story problems, conducting documentation to obtain accurate data when in the field by classifying students' mathematical representative abilities based on math scores. The results showed that most learners had a very good level of cognitive ability in completing arithmetic operations, but there were some learners who were still lacking in understanding story problems. This finding confirms that the importance of appropriate learning strategies so that learners are not only able to solve problems in the form of operations but also able to understand problems in the form of story problems that are applied in real life.